P2.161 Exploring the Acceptability of Online STI Testing For Rural Young People in Victoria. (13th July 2013) - Tomnay, J E; Bourke, L; Fairley, C K
Abstract : Background: Rural young people living in Australia experience disadvantage in service access for STI testing and treatment. As such, innovative programmes using telemedicine have been developed but results show relatively low usage. Websites offering free online STI testing address issues of access; however acceptability of these services to rural young people is unknown. Method: Participants were recruited from small country towns in Victoria and grouped by gender and age. During focus groups participants were asked to discuss their access to local sexual health services (what services they used, when, why and how) and then shown a website and asked to provide feedback about online STI testing. Results: Fifty participants from two small rural towns in Victoria were interviewed via seven focus groups. Both towns have GP services but no specialist sexual health services. Six main themes emerged in relation to acceptability of online STI testing. These were (1) readiness to seek sexual health services (2) credibility of the website, (3) using the mail during online STI testing, (4) getting the test results, (5) cost of the online service and (6) using the local GP versus using online testing. The participants identified a number of factors that may influence the use online services including the availability and acceptability of existing local services and whether the website looks credible, is confidential and free. In general the participants described some concerns about accessing sexual health services locally. This was less discussion about availability of services and more about privacy, trust, reliability and using generalist health care providers for sexual health needs. Conclusion: Free online testing services address issues of access for rural young people. While barriers external to rural sexual health services may remain, free online STI testing services are acceptable to these rural young people.